2013
DOI: 10.1002/arco.5003
|View full text |Cite
|
Sign up to set email alerts
|

The sherds of conquistadors: a petrological study of ceramics from Graciosa Bay and Pamua, Solomon Islands

Abstract: We present evidence linking vessel forms with ceramic wares resulting from the petrological analysis of 33 sherds from two sixteenth century Spanish colonial sites in the Solomon Islands. Our results expand the range of fabric types previously published, and comparative literature analyses support earlier studies suggesting probable ceramic origins in the Americas and Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Through the comparison of typological and petrological data with the published literature (Dickinson and Green ; Green ; Kelloway et al ; Kelloway ), U–Pb dating of detrital zircons (Kelloway et al ) and the chemical data presented in this paper, we suggest that many of the ceramics within the Solomon Islands artefact assemblages were made variously within Peru, Spain, Panama, China and Thailand. Many of the various types are Peruvian made, and the other non‐Peruvian‐made ceramics would have been readily obtained within Peru.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Through the comparison of typological and petrological data with the published literature (Dickinson and Green ; Green ; Kelloway et al ; Kelloway ), U–Pb dating of detrital zircons (Kelloway et al ) and the chemical data presented in this paper, we suggest that many of the ceramics within the Solomon Islands artefact assemblages were made variously within Peru, Spain, Panama, China and Thailand. Many of the various types are Peruvian made, and the other non‐Peruvian‐made ceramics would have been readily obtained within Peru.…”
Section: Discussionsupporting
confidence: 56%
“…Based on the geochemical results presented in this paper and typological and petrological studies carried out in the 1970s and more recently (Dickinson and Green ; Green ; Bedford et al ; Kelloway et al ; Kelloway ), a number of suggestions can be made as to the provenance(s) of various wares in the Solomon Island assemblages. The Asian Stoneware originated from Thailand based both on typological and geochemical comparisons, and the porcelain is most likely Ming porcelain from China, based on typology.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…With respect to Panama, although the younger rocks of Panama could yield granitic sands and abundant zircons, the majority of zircons in this study are pre-Eocene. Further, no sedimentary-metasedimentary lithics were identified in thin sections of the main INAA group sherds (Dickinson & Green, 1973;Kelloway, Gibbs, & Craven, 2013). Rather, the rock fragments in the olive jars under study are igneous suggesting derivation from a granitic source and the Panamanian granitic rocks are not as voluminous as Peruvian batholiths.…”
Section: Comparative Geologymentioning
confidence: 95%
“…In this study, we apply the methodology of U-Pb zircon dating to further determine the provenance of Red Earthenware olive jars (botijas) retrieved from two 16th Century colonial Spanish sites in the Solomon Islands (Allen, 1976;Allen & Green, 1972;Green, 1973). Previous research involving petrology and geochemistry (INAA) indicated possible Panamanian or Peruvian origins for these sherds (Bedford et al, 2009;Dickinson & Green, 1973;Kelloway, Gibbs, & Craven, 2013). This paper presents U-Pb ages of zircons extracted from five Red Earthenware sherds that indicate an Andean origin, and some implications for our understanding of production and distribution of 16th Century Peruvian-made pottery.…”
Section: Introductionmentioning
confidence: 99%